Sinergi Etika Bisnis Islam, Fiqih Muamalah, dan Hukum Perikatan dalam Mendorong Pertumbuhan Ekonomi Syariah di Indonesia - Dani Mulyana (Ikatan Da'i Indonesia, 2026)
This article discusses the synergy between Islamic business ethics, muamalah jurisprudence, and contract law in encouraging the growth of sharia economy in Indonesia. Islamic business ethics serve as a moral guideline, ensuring that economic activities are carried out fairly, transparently, and socially responsible. Muamalah jurisprudence provides a legal framework that regulates various forms of transactions in accordance with sharia principles, such as mudharabah, musyarakah, and ijarah contracts. Contract law in Islam complements both by providing certainty and legal protection in every agreement made. This synergy creates a safe, stable, and competitive business ecosystem, which increases public trust in the sharia economic system. With support from the government, financial institutions, and the community, this synergy is able to strengthen sharia financial literacy and encourage an inclusive economy. As a result, Indonesia has the potential to become a global center for sharia economy by creating inclusive and sustainable economic growth.